Research on Value Integration Mode of Agricultural E-Commerce Industry Chain Based on Internet of Things and Blockchain Technology - Li, Xiaochun; Huang, Dan (Wireless Communications and Mobile Computing, 2020)
With the development of Internet technology, especially the application of mobile Internet technology in people’s daily lives, people’s lifestyles and production methods have changed, and they have brought huge economic benefits to society. In order to improve the development quality of agricultural e-commerce and expand the integration model of e-commerce, the paper analyzes the development and changes of Internet technology in the agricultural industry chain from the source to operation, production, service, security, and sales and studies the production experience model iterative upgrade. At the same time, a blockchain-based agricultural product traceability system is proposed. The system has a good supervision effect. Once recorded on the blockchain ledger, all data cannot be changed, which plays a very good traceability role for agricultural e-commerce. Actual cases show that the integrated model of agricultural e-commerce based on blockchain technology can bring huge development potential to the e-commerce industry and can improve the security and traceability of agricultural e-commerce.